2013
DOI: 10.1007/s00432-013-1477-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of lung cancer in HIV-infected patients

Abstract: Our study suggests an increase in the incidence and risk of lung cancer in HIV/AIDS population is worldwide. The effect of HAART on the incidence and risk of lung cancer is in dispute. The risk of lung cancer based on gender differences, especially among females, as well as IDUs, requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 95 publications
0
12
0
1
Order By: Relevance
“…124 Lung cancer risk also was greater among HIV-infected individuals compared with the general population. Standardized incidence ratio comparing the number of observed to expected cases, or adjusted the IRR, was 5.0 in Africa, and ranged from 0.7 to 6.9 in the United States and 1.5 to 3.4 in Europe.…”
Section: Site-specific Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…124 Lung cancer risk also was greater among HIV-infected individuals compared with the general population. Standardized incidence ratio comparing the number of observed to expected cases, or adjusted the IRR, was 5.0 in Africa, and ranged from 0.7 to 6.9 in the United States and 1.5 to 3.4 in Europe.…”
Section: Site-specific Cancersmentioning
confidence: 99%
“…Although highly active antiretroviral therapy significantly prolongs survival of HIV-infected individuals, its impact on lung cancer risk and incidence is not clear. Although the review by Hou et al 124 did not directly address potential differences in risk between sexual minorities and heterosexual populations, many of the studies included were conducted among gay men. There are no other published data on the influence of other established lung cancer risk factors 114 , such as occupational exposures, radon, asbestos, and family history, among sexual minorities.…”
Section: Site-specific Cancersmentioning
confidence: 99%
“…The evidence regarding the degree of immunosuppression (based on CD4 + T-cell counts) as a risk factor for lung cancer is controversial. Several studies showed that the degree and duration of immunodeficiency and low CD4 + T-cell counts (< 200–500/mm 3 ) is associated with lung cancer risk 116,117 , whereas others failed to come to the same conclusion when adjusted for smoking and age 108,118,119 .…”
Section: Etiologic Agents and Pathogenesismentioning
confidence: 99%
“…The spectrum of intrathoracic HIV-related malignancies appears to be similar in resource-poor and rich settings, and includes pulmonary Kaposi sarcoma (KS) and pulmonary lymphoma. [96][97][98][99][100] Data on the relationship between HIV and bronchopulmonary lung cancer, are heavily confounded by exposures, such as cigarette smoking and drug use. However, there is a clear excess of lung cancer in the veterans aging cohort study, and it appears likely that HIV infection is a direct risk factor for these malignancies.…”
Section: Lung Malignancymentioning
confidence: 99%
“…However, there is a clear excess of lung cancer in the veterans aging cohort study, and it appears likely that HIV infection is a direct risk factor for these malignancies. 58,97,101 Measurement of the prevalence and incidence of pulmonary malignancy in resource-poor settings is challenging: these are relatively rare events for which large cohorts or case-control analyses are required, and the comprehensive cancer registries that have provided much data in resource-rich settings are not widely available in LMIC. 102 In addition, complex imaging and histopathology are required to make these diagnoses, and neither are easily accessed in resource-poor environments.…”
Section: Lung Malignancymentioning
confidence: 99%